Use of Nano Aqua Citrates for Optimization of Endoparasite of Chouioia Cunea Jang. (Hymenoptera: Eulophidae) - Мороз, М. С.; Максін, В. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
We presented the results of researches of influence of nano aqua citrate germanium; magnesium; selenium on the technological parameters of cultivation and maintenance of nourishing internals of pupas of phytophage-ownere on condition of their use for the continuous breeding of Chouioia cunea Jang. At the use of nano aqua citrates we provide a special purpose operating on the culture of Chouioia cunea Jang. optimal terms of maintenance; dynamic equilibrium with an environment; adjustment of biological efficiency of endoparasite. According to research results; we observed in experimental ways the maximum performance of phenol oxidize activity of protective cells of hemolymph of phytophage-ownere; biological effectiveness; reproductive capacity and endoparasites tolerance to changes in environmental factors during ontogenesis. For additional nutrition nano aqua citrate magnesium 0;0001- 0.0005 %% phenol oxidize concentration of activity in protecting cells hemolymph Antheraea pernyi G.-M. was 13;02- 14;51%. Maximum degree of contamination of pupae Hyphantria cunea Drury. - 94%; reproductive potential of endoparasites Chouioia cunea Jang . when grown on phytophage-ownere Antheraea pernyi G.-M. - 19465 individuals; that is 50.89% more compared with control option. For use as bioactive components nano aqua citrate germanium; magnesium and selenium in the postembryonic growth of phytophage-ownere we set the best performance to preserve the nutritional quality of pupae for nutrition after long-term storage.